(untitled) (Principles and Practice of Clinical Research, 2022)
Background: Achilles and patellar tendinopathy are the most common musculoskeletal disorders in lower extremities, with numerous therapeutic modalities for treatment and management. Nowadays, cell-based therapies like stem cells (SC) and platelet-rich plasma (PRP) have satisfactory clinical outcomes. Aim: To perform a meta-analysis of randomized controlled clinical trials to determine the functional efficacy of cell therapy (SC or PRP) in patellar (PT) and Achilles tendinopathy (AT). Study Design: Meta-analysis. Methods: PubMed, Cochrane Library, Google Scholar, SciELO, International Clinical Trials Registry, Clinical Trials.gov, and Lilacs were searched from January 2010 to May 2021. Reference lists were manually checked. Randomized controlled trials (RCTs) using SC and PRP to treat tendinopathy using the Victorian Institute of Sport Assessment (VISA) for patellar (VISA-P) and Achilles (VISA-A) tendinopathy were included. Published RCTs using other treatment modalities, non-tendon condition, non-per-protocol analysis, and other studies designs were excluded. Study quality was assessed using the CONSORT 2010 checklist for reporting a randomized trial. The Cochrane Collaboration risk of bias tool for randomized trials was used, and two review authors assessed their quality. The effect size was reported as a standardized mean difference (SMD) in a random effect model. The sensitivity analysis for publication bias was evaluated. A funnel plot was used, and Egger´s regression test was performed for asymmetry evaluation. Results: A total of eight RCTs with cell therapy were considered. The studies included a total of 318 patients with PT and AT with a mean follow-up of 28.75 (+-11.82) weeks. There was no significant difference between the two groups in the random-effects model (SMD=0.43, 95%CI (-0.52, 1.37), t=1.07, p=0.32). No significant difference between subgroups analysis considered the type of regenerative therapy (Q=3.49, df=2, p=0.17), and injection site (Q=0.36, df=1, p=0.55) were detected. Conclusion: This meta-analysis does not provide enough evidence to support the use of cell therapy (SC and PRP) to manage PT and AT. Keywords: Achilles, Patellar, Platelet-rich plasma, Tendinopathy, VISA.